PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA CONSUMER GOODS SECTOR - Prafidhya Dwi Yulianto; Lilik Ambarwati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The purpose of this research is to know the influence of Working Capital Management on Profitabilty in Consumers Goods listed on the Bursa Efek Indonesia (BEI) aims to analyze the influence of woring capital in the from of: Cash Turnover, Account Receivable Turnover, and Inventory Turnover to Profitability (Return On Asset) at Consumers Goods Sector. This research method uses multiple linear regression analysys with the help of SPSS 23.00 software which is used to see the inflyence between the independent variables in the from Cash Turnover, Account Recevaible Turnover, and Inventory Turnover to Return On Asset (ROA)). The sample of this research is 31 consumer goods sector in 2015-2018, so there are 124 annual report obtained through purposive sampling, then analyzed using multiple linear regression methods. The result showed thad based on the F test, the independent variable had an effect on the ROA, it is indicated of 6.765 and significance of 0.000, overall the independent variable was able to eaplain the effect 59,60 percent. While based on the partial t test, shows that the variable Cash Turnover, Account Recevaible Turnover, and Inventory Turnover has a positive and siginificant effect on Profitability.